THE ORIGINS OF ULTRAPOTASSIC ROCKS AS INFERRED FROM SR, ND AND PB ISOTOPES - Nelson D.R.; Mcculloch M.T.; Sun S.S. (My University, 1986)
Pb, Nd and Sr isotopic compositions are reported for ultrapotassic rocks from a variety of tectonic settings. Olivine leucitites located within the Palaeozoic Lachlan Fold Belt of southeastern Australia have a range in initial of from 0.7042 to 0.7056, ϵNd values of + 1.5 to −4.1 and of 15.55 to 15.60. These isotopic characteristics overlap with those of contemporaneous alkali basalts and suggest derivation of the leucitites from sources which have been variably contaminated by either the hotspot which initiated volcanism or during earlier enrichment events. Lamproites from the West Kimberley region of Western Australia and leucitites from Gaussberg intrude stabilised Precambrian continental crust and have low (<17.86 and <17.60 respectively and high (>15.69 and >15.65). Pb isotope correlations displayed by the Western Australian lamproites are consistent with the mixing of an ancient (>2.1 byr old) high , low component with more typical mantle Pb. These ancient components probably evolved within the subcontinental lithosphere. Lamproites from southeastern Spain, which have geochemical features (i.e. negative Ti- and Nb-anomalies) suggesting a subduction-related origin, possess isotopic compositions ( = 0.7173 to 0.7207, , and ϵNd = −11.2 to−12.6) and isotope correlations consistent with contamination of their sources by a component resembling modern oceanic sediments. This component is isotopically similar to that previously identified in the potassic rocks of Italy. A leucitite from a back-arc setting in the Sea of Japan has Pb isotopic composition similar to some ocean islands such as Kerguelen. The available isotopic data from this and other studies implicate enrichment processes frequently involving ancient, isotopically evolved components in the generation of continental potassic magmatism. These components are probably polygenetic with possible sources including subducted sediments, “megaliths” of recycled crust or the subcontinental lithosphere
Keywords: Precambrian; Palaeozoic; Precambrian; Paleozoic; Палеозой; Докембрий